Entomopathogenic Nematology - Gaugler, R.; Ebooks Corporation (Wallingford : CABI, 2001)
This text provides a comprehensive review of entomopathogenic nematology. It reviews fundamental biology; setting a taxonomic foundation for nematodes and their bacterial processes involved in parasitism and to nematode ecology, and describes technological advances and control methodologies.
Contenido: 16 Factors Affecting Commercial Success: Case Studies in Cotton, Turf and Citrus17 The Biosys Experiment: an Insider{80}{99}s Perspective; Index
Libro electronico adquirido a perpetuidad con la editorial CABI
Keywords: NEMATODOS